Perceived stress, psychological resilience, hair cortisol concentration, and metabolic syndrome severity: A moderated mediation model. (March 2020) - Lehrer, H. Matthew; Steinhardt, Mary A.; Dubois, Susan K.; Laudenslager, Mark L.
Highlights: In a sample of White, Hispanic, and African American adults, hair cortisol concentration was associated with greater metabolic syndrome severity. Perceived stress was associated with greater hair cortisol concentration, but only for low-resilience participants. Resilience moderated the indirect association of perceived stress with greater metabolic syndrome severity via elevated HCC. Abstract: Background: Psychological resilience is considered to protect against detrimental effects of perceived stress on cardiovascular and metabolic health, but few studies have tested biological mechanisms underlying these relationships. Purpose: This study examined whether psychological resilience moderated the indirect association of perceived stress with Metabolic Syndrome (MetS) severity via hair cortisol concentration (HCC), a retrospective index of hypothalamic pituitary adrenal (HPA) axis activity. Method: Participants included 228 adults (73 White, 86 Hispanic, 69 African American; mean age 45.29 years; 68% females). Participants completed questionnaires assessing perceived stress (Perceived Stress Scale) and resilience (Brief Resilience Scale). The first 3 cm of scalp-near hair were analyzed for cortisol concentration using enzyme-linked immunoassay analysis. Cardiometabolic risk factors including blood glucose, lipids, blood pressure, and waist circumference were assessed, from which a sex- and race/ethnicity-specific continuous MetS severity score was calculated. A moderated mediation model was tested using path analysis. Results: Psychological resilience moderated the association of perceived stress with HCC ( R 2 change for interaction = 0.014, p  =  0.043), such that the association of perceived stress and HCC decreased as resilience scores increased. Resilience also moderated the indirect association of perceived stress with MetS severity via HCC ( b = -0.039, 95% CI [-0.001; -0.100]), such that HCC mediated the association of greater perceived stress with greater MetS severity only for individuals reporting Brief Resilience Scale scores 3 or below (range: 1.17–5.00). Psychological resilience was also associated with lower MetS severity ( β = -0.227, p  =  0.014) independent of perceived stress and HCC. Conclusion: Findings suggest that psychological resilience may serve as both a stress buffer and as a direct determinant of cardiometabolic health. These results extend literature on psychological resilience to measures of retrospective HPA axis function and MetS severity in a diverse sample.